RETIREMENT BENEFITS CALCULATIONS FOR STATE EMPLOYEES USING MICROSOFT VISUAL BASIC IN PT.TASPEN - Nanang Fachrurrozi; Ir. Fitri Sjafrina, SKom, MMSI (Jurnal Sistem Informasi, 2004)
Was arranged with the intention of helping officers in the process of making the calculation of retirement benefits in the civil bagipegawai instansinya based on predetermined age limit. Head of financial department to make the calculation of retirement benefits for civil servants using Visual Basic 6.0 applications.